Implementation of POE Learning Model with Worksheets Assistance to Improve Students’ Activities and Learning Outcomes - Fatwadi, Agus; Gummah, Syifaul; Prasetya, Dwi Sabda Budi (Lensa : Jurnal Kependidikan Fisika, 2019)
The purpose of this study is to improve the students? activity and learning outcomes through the implementation of the POE learning model with the assistance of student worksheets. The research subjects were 22 students? grade of VIII SMP Negeri 4 Batukliang Utara. This type of research is classroom action research (CAR), which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation/evaluation, and reflection. The implementation of the POE learning model is carried out through three stages, namely Predict, Observe, and Explain stages. The measured variable is the activity and learning outcomes on the subject matter of Motion. Research data collection techniques using observation sheets and tests. The results of the study in Cycle I obtained an average score of student learning activities is 2.08 with the category of quite active and the average value of students? learning outcomes is 73.41 with classical completeness of 54.55%. In cycle II the average score of students? learning activities is 2.95 with the actively category and the average learning outcome is 83.41 with a classical completeness of 86.36%. Based on the results of the study it was found that the implementation of the POE learning model with the worksheets assistance could improve the students? activities and learning outcomes grade of VIII SMPN 4 Batukliang Utara.